Tinjauan Pustaka: Karakteristik Dan Respon Antibodi Vanksin Dengan Sediaan Microneedle Patch - Lika Ginanti Febriana (Berkala Ilmiah Mahasiswa Farmasi Indonesia, 2022)
Introduction: Vaccination is one of the greatest medical advances of modern preventive medicine. Vaccination is the most effective way to control the incidence of infectious diseases. However, the current vaccination approach faces a number of challenges that impact vaccination compliance. Most vaccines given by intramuscular (IM) or subcutaneous (SC) injection cause pain and discomfort, in most cases, leading to poor adherence due to needle phobia. The development of microneedle patch technology has been applied to various types of vaccines. Methods: The research method used is literature review. The literature sources used in this study were searched through the PubMed® and Google Scholar databases with the keywords microneedle vaccine, vaccine patch, and microneedle patch vaccine. Found 20 articles that can be used in the literature review Result: The results of research on the microneedle patch from various types of vaccines need to be studied to determine the effectiveness of the vaccine in the form of a microneedle patch. Various aspects such as the type of microneedle patch, needle height, and antibody response to vaccine preparations in the form of a microneedle patch can be indicators to assess the potential of a microneedle patch. Conclusion: Various aspects such as the type of microneedle patch, needle height, and antibody response to vaccine preparations in the form of a microneedle patch can be used as indicators to assess the potential of a microneedle patch. There are four types of microneedle, namely Solid Microneedle, Coated Microneedle, Dissolving Microneedle, and Hollow Microneedle. To penetrate the skin, the microneedle has a pointed tip with a length of 150-1500 m, a width of 50–250 m, and a tip thickness of 1–25 m. Microneedle patch can induce antibody formation to be faster.. Keywords: Microneedle Patch, Vaccine, Vaccination